2010
DOI: 10.1007/s11172-010-0339-1
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition of diazoacetates to C60 fullerene catalysed by Pd complexes

Abstract: An efficient catalytic method of the cycloaddition to C 60 fullerene of the diazoacetates, containing substituents of diverse structures in ester groups, in the presence of a Pd based three component catalyst was developed. An influence of nature and the structure of substi tuent in the ester group on the activity of diazoacetates in the reaction with C 60 was studied. Yields of respective cycloadducts were determined.An interest in carboxy derivatives of methanofullerenes is caused by a possibility of obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The use of metal complex catalysts makes it possible to direct the cycloaddition of diazo compounds to fullerenes toward formation of individual methanofullerenes. Complexes based on palladium and rhodium were reported to successfully catalyze reactions of fullerene C 60 with diazomethanes [3], diazoacetates [4][5][6][7], and diazo ketones [8-10], and the corresponding cyclopropafullerenes were obtained with high selectivity.We recently showed that homofullerenes and spiro homofullerenes can be synthesized with high selectivity by reaction of C 60 with monosubstituted diazomethanes and cyclic diazoalkanes generated in situ by oxidation of the corresponding hydrazones in the presence of Pd(acac) 2 -PPh 3 -Et 3 Al as catalytic system [11][12][13][14][15][16]. We thus obtained pure [5,6]-open cycloadducts in which bulkier substituent was located above the five-membered fragment of C 60 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of metal complex catalysts makes it possible to direct the cycloaddition of diazo compounds to fullerenes toward formation of individual methanofullerenes. Complexes based on palladium and rhodium were reported to successfully catalyze reactions of fullerene C 60 with diazomethanes [3], diazoacetates [4][5][6][7], and diazo ketones [8-10], and the corresponding cyclopropafullerenes were obtained with high selectivity.We recently showed that homofullerenes and spiro homofullerenes can be synthesized with high selectivity by reaction of C 60 with monosubstituted diazomethanes and cyclic diazoalkanes generated in situ by oxidation of the corresponding hydrazones in the presence of Pd(acac) 2 -PPh 3 -Et 3 Al as catalytic system [11][12][13][14][15][16]. We thus obtained pure [5,6]-open cycloadducts in which bulkier substituent was located above the five-membered fragment of C 60 .…”
mentioning
confidence: 99%
“…The use of metal complex catalysts makes it possible to direct the cycloaddition of diazo compounds to fullerenes toward formation of individual methanofullerenes. Complexes based on palladium and rhodium were reported to successfully catalyze reactions of fullerene C 60 with diazomethanes [3], diazoacetates [4][5][6][7], and diazo ketones [8][9][10], and the corresponding cyclopropafullerenes were obtained with high selectivity.…”
mentioning
confidence: 99%
“…As a follow-up to the ongoing work in our group [13][14][15][16][17][18][19][20] related to the selective functionalization of C 60 -fullerene with diazo compounds, we studied the catalytic cycloaddition reaction of sulfur-containing diazoalkanes generated in situ by the oxidation of hydrazones of the corresponding ketosulfides with MnO 2 to C 60 . Of the tested catalysts based on salts 2 of 11 and compounds of Cu, Pd, and Rh, the three-component catalyst prepared in situ from Pd(acac) 2 , PPh 3 , and Et 3 Al, taken in a ratio of 1:2:4, respectively, showed the highest activity in the reaction of diazoalkanes and C 60 -fullerene.…”
Section: Resultsmentioning
confidence: 99%